ORGANIZATION OF ONLINE TUTORING OF THE ADAPTATION PROCESS OF FIRST-YEAR STUDENTS WITH DISABILITIES AND DISABILITIES - G. Kozlovskaya; E. Em (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the features of the organization of a complex of social, psycho-logical-pedagogical, educational support for students with disabilities and students with disabilities using the resources of the electronic educational environment of the university. The goals, content, means of implementing the main directions of tutoring support for students with disabilities, as well as the conditions for the effectiveness of online tutoring are considered. The experience of using social networks and volunteer mentors providing online consultations is presented. The authors focus on the issues of tutor support for the adaptation offirst-year students with disabilities and disabilities to educational activities in a higher educational institution by means of digital technologies and technologies of an inclusive electronic educational environment.